2018
DOI: 10.3390/agronomy8060087
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Barley Cover Crop Residue and Herbicide Management on the Foliar Arthropod Community in No-Till Soybeans

Abstract: Cover cropping has long been used as a method of reducing soil erosion, increasing soil quality, and suppressing weeds. However, the effects of cover crops in local farming systems are varied and can be affected by timing and method of termination. Field experiments were conducted at two sites in Maryland, USA during the 2013 and 2014 growing seasons to examine how varying the date and method of terminating a barley (Hordeum vulgare) cover crop affects the arthropod communities in succeeding no-till soybean (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Similar to some previous findings, results from this study showed no effect or a variable response of cover crops and residue disturbances on arthropod abundance in soybeans [ 23 , 40 , 41 ]. Overall, an increased abundance of all arthropods (cumulative feeding guilds) was recorded in the CC treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to some previous findings, results from this study showed no effect or a variable response of cover crops and residue disturbances on arthropod abundance in soybeans [ 23 , 40 , 41 ]. Overall, an increased abundance of all arthropods (cumulative feeding guilds) was recorded in the CC treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Chloramides (e.g., metolachlor, acetochlor, and pretilachlor) are among the most commonly used herbicide types. However, chloramides negatively affect the yield and growth of crops such as sweet potato, sorghum, wheat, soybean, corn, and rice [2][3][4][5][6]. Technologies that can combat the poor selectivity of herbicides include selective conventional herbicides and herbicide safeners [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…At present, most studies on landscape heterogeneity focus on the effects of overall landscape heterogeneity (including all land use types) or on the effects of the proportion of natural and semi-natural habitats [22][23][24], while there are fewer studies on crop habitat heterogeneity [25]. Research on the effects of crop habitat heterogeneity on pest control is also often concentrated at the small scale (field scale), such as in field-scale intercropping experiments [15,19,26].…”
Section: Introductionmentioning
confidence: 99%